Hurt people hurt people: ostracism and aggression. (February 2018) - Ren, Dongning; Wesselmann, Eric D; Williams, Kipling D
Highlights: We provide an overview of the core findings on ostracism-related aggression. We organize the literature using the temporal need-threat model of ostracism. There is substantial empirical evidence that ostracism may lead to aggression. Much of current research concentrates on investigating processes and moderators. An emerging body of literature seeks to develop aggression-reduction interventions. Abstract : Because ostracism hurts, it can trigger aggression. Guided by the theoretical framework of the temporal need-threat model of ostracism, we review the existing research that investigates this ostracism–aggression link over the last two decades. Both correlational and experimental research have provided substantial support for the model's prediction that ostracism may instigate aggression. Recent research continues to investigate why this occurs, and who is most likely to become aggressive when ostracized. A new and exciting body of literature emerges, which seeks to inform interventions for coping with ostracism and for reducing ostracism-related aggression.